WSN Gait Monitoring for Objective Evaluation of Rehabilitation Process - Postolache, Octavian (2015)
A survey of wireless sensor network solutions for gait assessment is presented including own developed solution gait assessment based on smart insoles nodes ZigBee compatible characterized by multichannel force measurement and MEMS inertial measurement IMU. The system was developed to measure ground reaction force, acceleration and direction of feet in order to provide information to physiotherapists for an objective evaluation of rehabilitation effectiveness. Based on acquired data from the sensing channels a set of gait feature extraction such as walking speed stride length, swing time are calculated as part of gait analysis. Software for WSN node control, gait feature calculation and primary analysis of rehabilitation effectiveness developed for the physiotherapist was designed and implemented and preliminary tests were carried out for normal and simulated anomalous gait.